Evaluation of a healthy ageing intervention for frail older people living in the community. (3rd December 2014) - McNamara, Beverley; Rosenwax, Lorna; Lee, Elinda AL; Same, Anne
Abstract : Aim: To evaluate a healthy ageing intervention in the form of a program of physical and social activity for frail older people living in the community. Methods: New members of an activity program were surveyed before and after attending the program and interviewed face‐to‐face prior to the program, immediately after the program and through a telephone interview two months following the program. Results: Program participants reported better health, social function and mental well‐being; greater engagement in household and leisure activities; and increased enjoyment and confidence through participating in the program. Some participants could not attend the whole program due to poor health or difficulties securing transport. Conclusion: The results suggest the program was successful in enhancing the health and well‐being of those community‐dwelling older adults who stayed in the program. However, the high drop‐out rate suggests that flexibility is required in community‐based healthy ageing programs.